Proteome and secretome analysis of pancreatic cancer cells. Issue 13 (14th April 2022) - Li, Xiang; Liu, Hui; Dun, Matthew D.; Faulkner, Sam; Liu, Xiaoming; Jiang, Chen Chen; Hondermarck, Hubert
Abstract: Pancreatic cancer is a lethal malignancy and no screening biomarker or targeted therapy is currently available. Here, we performed a shotgun proteomic label‐free quantification (LFQ) to define protein changes in the cellular proteome and secretome of four pancreatic cancer cell lines (PANC1, Paca44, Paca2, and BXPC3) versus normal human pancreatic ductal epithelial cells (HPDE). In the cellular proteome and secretome, 149 and 43 proteins were dysregulated in the most cancer cell lines, respectively. Using Ingenuity Pathway Analysis (IPA), the most dysregulated signaling pathways in pancreatic cancer cells included the activation of epidermal growth factor receptor (EGFR), phosphoinositide 3‐kinase (PI3K), protein kinase B (AKT), extracellular regulated kinase (ERK), and the deactivation of type‐I interferon (IFN) pathways, which could promote cancer cell progression and decrease antitumor immunity. Parallel reaction monitoring (PRM) mass spectrometry was used to confirm the changes of seven regulated proteins quantified by LFQ: EGFR, growth/differentiation factor 15 (GDF15), protein‐glutamine gamma‐glutamyltransferase 2 (TGM2), leukemia inhibitory factor (LIF), interferon‐induced GTP‐binding protein Mx1 (MX1), signal transducer and activator of transcription 1 (STAT1), and serpin B5 (SERPINB5). Together, this proteomic analysis highlights protein changes associated with pancreatic cancer cells that should be further investigated as potential biomarkers or therapeutic targets.